A new Bent-toed gecko (Squamata: Gekkonidae) from the Mekongga Mountains, South East Sulawesi, Indonesia - Riyanto, Awal; Kurniati, Hellen; Engilis, Jr, Andrew (Zootaxa, 2016)
We describe Cyrtodactylus hitchi sp. nov., a new species of Bent-toed Gecko from montane forests in the Mekongga Mountains, South East Sulawesi, Indonesia. Although we cannot speculate about relationships, morphologically it shares several traits with C. batik, a large species known only from Mount Tompotika near the tip of Sulawesi’s Eastern Peninsula. The following unique combination of characters distinguishes it from all other congeners: absence of precloacal groove, absence of precloacal and femoral pores, absence of enlarged femoral scales, no abrupt contact between large and small postfemoral scales, 18–20 lamellae under the fourth toes, and transversely enlarged, median subcaudal scales arranged in a single row.